Diagnosis and management of typical and atypical lung carcinoids. (April 2016) - Pusceddu, Sara; Lo Russo, Giuseppe; Macerelli, Marianna; Proto, Claudia; Vitali, Milena; Signorelli, Diego; Ganzinelli, Monica; Scanagatta, Paolo; Duranti, Leonardo; Trama, Annalisa; Buzzoni, Roberto; Pelosi, Giuseppe; et al.
Highlights: Typical and atypical carcinoids represent 1–5% of all lung malignancies. Surgery is the treatment of choice for loco-regional disease. Advanced lung carcinoids requires a multidisciplinary approach. No recognized standard of care is available for advanced lung carcinoids. Abstract: An estimated 20% to 30% of all neuroendocrine tumours originate in the bronchial tree and lungs. According to the 2015 World Health Organization categorization, these tumours are separated into four subtypes characterized by increasing biological aggressiveness: typical carcinoid, atypical carcinoid, large-cell neuroendocrine carcinoma and small-cell carcinoma. Although typical and atypical lung carcinoids account for less than 1–5% of all pulmonary malignancies, the incidence of these neoplasms has risen significantly in recent decades. Surgery is the treatment of choice for loco-regional disease but for advanced lung carcinoids there is no recognized standard of care and successful management requires a multidisciplinary approach. The aim of this review is to provide a useful guide for the clinical management of lung carcinoids.